PP.27.08: THE BINDING BETWEEN FIBRINOGEN AND THE ERYTHROCYTE RECEPTOR ASSESSMENT IN ESSENTIAL ARTERIAL HYPERTENSION. (June 2015) - Moreira, C. Santos; Guedes, A. Filipa; Carvalho, F.; Braz-Nogueira, J.; Santos, N.C.
Abstract : Objective: Several cross-sectional studies have reported a positive association between plasma fibrinogen levels, erythrocyte aggregation and arterial hypertension. Fibrinogen-induced erythrocyte aggregation might be relevant in essential arterial hypertension (EAH) as potential prognostic biomarker and on future drug interventions to reduce aggregation and enhance microcirculatory flow conditions. Our previous studies have shown that an all bbeta3-like integrin is a specific receptor for fibrinogen on the erythrocyte membrane. The aim of the present study was to understand how the interactions between fibrinogen and the specific erythrocyte membrane receptor are altered on EAH. Design and method: Fibrinogen-erythrocyte adhesion was evaluated quantitatively using atomic force microscopy (AFM)-based force spectroscopy. This is a single-cell molecular technique that allows the measurement of the force and the binding frequency of the fibrinogen-erythrocyte adhesion. Data from patients and healthy donors were collected and compared using Student's T-test. Results: Essential arterial hypertension patients (N = 31) and healthy blood donors (N = 15) were engaged in the study. EAH patients were individuals between the ages of 44 and 87, with systolic blood pressure between 108 and 180 mm Hg and/or diastolic blood pressure between 66 and 123 mm Hg. EAH patients were therapeutically controlled for the disease. No anti-platelet aggregation therapy was used. Force spectroscopy data showed that the average fibrinogen-erythrocyte binding forces increase from 40.4 ± 3.0 pN in healthy donors to 101.0 ± 7.1 pN in patients with EAH (p < 0.0001), despite a lower binding frequency for patients comparing to control group (27.6 ± 4.2 % vs. 9.0 ± 0.3 %; p < 0.0001). Conclusions: The increased fibrinogen adhesion to the erythrocytes from EAH patients may lead to changes on the whole blood flow, due to transient bridging of two erythrocytes by the simultaneous binding of fibrinogen to both of them, representing an important cardiovascular risk factor.